Early diagnosis of neonatal septicemia by hematologic scoring system, C-reactive protein and serum haptoglobin (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):85-92 The abstract of this article is available on the PubMed website